Anti-inflammatory action of HO-1/CO in human bronchial epithelium in response to cationic polypeptide challenge. (January 2019) - Zhang, Rui-Gang; Pan, Kewu; Hao, Yuan; Yip, Chung-Yin; Ko, Wing-Hung
Highlights: Cationic peptide exposure led to upregulation of HO-1 but not HO-2 expression. HO-1 induction or CORMs suppressed cationic peptide-induced IL-6 and IL-8 release. HO-1 knockdown further increased cationic peptide-induced IL-6 and IL-8 release. HO-1/CO axis exerts anti-inflammatory activity in human bronchial epithelium. Abstract: Carbon monoxide (CO) is an anti-inflammatory gaseous molecule produced endogenously by heme oxygenases (HOs) HO-1 and HO-2. However, the mechanisms underlying the anti-inflammatory effects of CO in the human bronchial epithelium are still not fully understood. In this study, the cationic peptide poly-l -arginine (PLA) was utilized to induce bronchial epithelial damage and subsequent pro-inflammatory cytokine release in the human bronchial epithelial cell line 16HBE14o-. Expression of both HO-1 and HO-2 after PLA exposure was examined. The polarized secretion of two pro-inflammatory cytokines, interleukin (IL)-6 and IL-8, was determined by ELISA. The anti-inflammatory effects of CO liberated from CO-releasing molecules (CORMs) were examined by both ELISA and western blot analysis. Our results indicate that PLA exposure leads to upregulation of HO-1 expression and p65 NF-κB phosphorylation, as well as IL-6 and IL-8 release. HO-1 induction by hemin or CORMs significantly suppressed IL-6 and IL-8 release. In addition, HO-1 knockdown further increased IL-6 and IL-8 release under basal and PLA-stimulated conditions. Our results thereby demonstrate that the HO-1/CO axis exerts significant anti-inflammatory activity during bronchial epithelial damage caused by cationic protein.